Morphological correlates of sex differences in acoustic startle response and prepulse inhibition through projections from locus coeruleus to cochlear root neurons - Hormigo, Sebastian; Gómez-Nieto, Ricardo; Sancho, Consuelo; Herrero-Turrión, Javier; Carro, Juan; López, Dolores E.; Horta-Júnior, Joséde Anchietade Castroe [UNESP] (Springer Nature, 2017)
The noradrenergic locus coeruleus (LC) plays an important role in the promotion and maintenance of arousal and alertness. Our group recently described coerulean projections to cochlear root neurons (CRNs), the first relay of the primary acoustic startle reflex (ASR) circuit. However, the role of the LC in the ASR and its modulation, prepulse inhibition (PPI), is not clear. In this study, we damaged LC neurons and fibers using a highly selective neurotoxin, DSP-4, and then assessed ASR and PPI in male and female rats. Our results showed that ASR amplitude was higher in males at 14 days after DSP-4 injection when compared to pre-administration values and those in the male control group. Such modifications in ASR amplitude did not occur in DSP-4-injected females, which exhibited ASR amplitude within the range of control values. PPI differences between males and females seen in controls were not observed in DSP-4-injected rats for any interstimulus interval tested. DSP-4 injection did not affect ASR and PPI latencies in either the male or the female groups, showing values that were consistent with the sex-related variability observed in control rats. Furthermore, we studied the noradrenergic receptor system in the cochlear nerve root using gene expression analysis. When compared to controls, DSP-4-injected males showed higher levels of expression in all adrenoceptor subtypes; however, DSP-4-injected females showed varied effects depending on the receptor type, with either up-, downregulations, or maintenance of expression levels. Lastly, we determined noradrenaline levels in CRNs and other LC-targeted areas using HPLC assays, and these results correlated with behavioral and adrenoceptor expression changes post DSP-4 injection. Our study supports the participation of LC in ASR and PPI, and contributes toward a better understanding of sex-related differences observed in somatosensory gating paradigms.
Keywords: Adrenergic receptors; ASR pathway; Catecholamines; Dopamine beta-hydroxylase; DSP-4; Noradrenaline; Somatosensory gating